Spatial-temporal distribution of tropical cyclone activity on the eastern sea area of China since the late 1940s. (31st October 2022) - Xu, Chaoran; Yang, Yang; Zhang, Fan; Li, Renzhi; Li, Zhanhai; Wang, Ya Ping; Jia, Jianjun
Abstract: Among all marine hazards, storm surges cause the most severe damage, and East Asia is one of the regions in the world most affected by tropical cyclones (TCs). With the increase in global mean temperature, the future changes of tropical cyclone (TC) activities are of great concern in East Asian countries. However, due to the inconsistency among different TC datasets, there is no uniform understanding of the spatial and temporal distribution and trends of TC activities in the eastern sea area of China (ESAC). In this study, all TC wind fields affecting ESAC during 1949–2019 were calculated using the Fujita-Takahashi formula, and a new TC dataset with a spatial resolution of 0.1° × 0.1° was thus obtained. Based on this dataset, the spatial-temporal variations of TC activity were analyzed. Three stages (1949–1967, 1968–1993, 1994–2019) of TC activities in ESAC can be identified using Mann Kendall Trend Test, which is closely related to El Niño-Southern Oscillation, sunspot activity, and Pacific Decadal Oscillation. A comparison of the accumulative number and duration of TCs in the three stages shows increasing trend toward the coasts and an northward. To address the issue of shelf storm deposition records on ESAC, we compared the published storm depositional records retrieved from several cores with typhoon impact data from the same sites based on the dataset of this study. We found that the preservation potential of the storm deposition record on ESAC ranged from 8% to 33%, with a high preservation potential in shallow water. These findings reveal the distribution and variability of TC impacts, which can be used to provide a scientific basis for disaster prevention and mitigation planning and adjustment of key coastal protection zones, as well as to evaluate the value of marine sedimentary records better. Graphical abstract: We have established a new and more comprehensive dataset (0.1° × 0.1°) to analyze the spatial-temporal distribution of tropical cyclone(TC) activity on the seas. Also due to the latitudinal and longitudinal effects of TC effect, the coastal cities in northern China may suffer from more severe storm surge disasters in the future. We also included sedimentary records to help us understand more ancient TC activity. Image 1 Highlights: We provide a new high-resolution (0.1° x 0.1°) and more detailed dataset of tropical cyclones. . Coastal cities in northern China are likely to suffer from more severe storm surge disasters in the future. The tropical cyclone dataset coupled with the sedimentary record can provide a better understanding of paleostorm activity.